2021
DOI: 10.1088/1742-6596/2130/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural network (ANN) for water quality index (WQI) prediction for the river Warta, Poland

Abstract: The aim of this paper is to present the potential of using neural network modelling for the prediction of the surface water quality index (WQI). An artificial neural network modelling has been performed using the physicochemical parameters (TDS, chloride, TH, nitrate, and manganese) as an input layer to the model, and the WQI as an output layer. The physicochemical parameters have been taken from five measuring stations of the river Warta in the years 2014-2018 via the Chief Inspectorate of Environmental Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In [24], experimental results pertaining to a Water quality index (WQI) estimation for the Bhavani River, India, showed that the applied artificial neural network (ANN) configuration outperformed their benchmarking models, providing superior accuracy and error values. A similar result was found in another work [25], where ANN was employed for WQI forecasting in Warta River, Poland. Their best-assessed ANN configuration used five hidden neurons in a multilayer perceptron (MLP) structure, returning a root mean square error (RMSE) value of 0.64, proving itself as an essential tool for surface water quality determination.…”
Section: Introductionsupporting
confidence: 86%
“…In [24], experimental results pertaining to a Water quality index (WQI) estimation for the Bhavani River, India, showed that the applied artificial neural network (ANN) configuration outperformed their benchmarking models, providing superior accuracy and error values. A similar result was found in another work [25], where ANN was employed for WQI forecasting in Warta River, Poland. Their best-assessed ANN configuration used five hidden neurons in a multilayer perceptron (MLP) structure, returning a root mean square error (RMSE) value of 0.64, proving itself as an essential tool for surface water quality determination.…”
Section: Introductionsupporting
confidence: 86%
“…A good performance is observed, suggesting that MLP is able to predict the South African water quality well. Similarly, an ANN is used in [ 34 ] to predict the WQI value of the Warta River in Poland, using five selected parameters, including the total dissolved solids (TDS), chloride, total hardness (TH), NO 3− , and manganese. The model obtained a 0.9792 correlation coefficient value.…”
Section: Related Workmentioning
confidence: 99%
“…Among them, the most favorable outcomes were attained with an ANN employing the softmax activation function and Adam's loss function optimizer, demonstrating an impressive performance with a MAPE of 9.6% and a coe cient of determination R2 of 0.964. Neural network modeling has been employed to predict the Surface WQI [3]. The arti cial neural network model utilized physicochemical parameters (TDS, chloride, pH, nitrate, and manganese) as the input layer and WQI as the output layer.…”
Section: Introductionmentioning
confidence: 99%